Пошук харизматичного образу в сакральній архітектурі Львова 1990–2000-х років - Франків, Роман; Frankiv, Roman (Видавництво Львівської політехніки, 2020)
У статті окреслено феномен пошуків харизматичного образу для сакральних об’єктів у львівській архітектурі межі 1990–2000-х років. Унікальною особливістю об’єктів, що постали в рамках цього феномену, стала свобода засобів та індивідуальних інтерпретацій, не скутих рамками канонічних та традиціоналістичних стереотипів, котрі на цьому ранньому етапі релігійного відродження були мало відомими та впливовими.

The article considers the issue of charismatic sacral architecture in Lviv within 1990–2000 years. It has been outlined a period, during which traditionalist or denominational stereotypes did not affect a process of the sacral building’s design. Within this, some unique structures have occurred, as a result of an individual search of a charismatic image of a sacral space. The active phase of this period lasted through the 1990s and 2000s. Consider this, design and architectural features of several sacred buildings in Lviv have been analyzed (Churches of Vladimir and Olga, Chiton of the Virgin, All Saints of the Ukrainian nation, Assumption of the Virgin). As a result of these searches, it can be argued the existence of a separate phenomenon of modernist charismatic church architecture in Lviv, the studies of which, have not yet been fully conducted. Charismatic images that emerged in Lviv church architecture of that time are characterized by a variety of ideas and techniques used. It is revealed that, although they are based on their interpretation of the sacred space, they also partially influenced by late Soviet neo-constructivism and of the work of the Ukrainian architect in the Canadian diaspora - Radoslav Zhuk. The architecture of these structures is characterized by the diversity of means of composition and the spontaneity of attempts to express, by modernistic language, some metaphysical matters. Since in the late 2000s, the tendency of the return to the formation of deterministic considerations of the historical identity of a particular denomination, and a certain typification of church morphology gradually emerged, it is established that the phenomenon of unique charismatic objects in the sacral architecture in Lviv, can be the subject of a deeper scientific and theoretical study.
Search for charismatic image in Lviv sacral architecture in the 1990s and 2000s
Keywords: образ; харизма; Львів; сакральна архітектура; image; charisma; Lviv; sacral architecture; modernism; 726